Proportion problems: analyzing common errors - Humaira Salsabila, Nilza; Lu’luilmaknun, Ulfa; Wahyu Triutami, Tabita; Hamdani, Deni; Ayu Apsari, Ratih (Journal of physics. Conference series, 2021)
Proportion problems are problems that are often found in real life. For that, we need to be able to solve problems related to proportion. But some of us make the mistake of solving problems about proportion. The purpose of this research is to identify the types of errors made by junior high school students working on proportion problems. The types of errors students make are identified based on the types of test-taking errors by Nolting. There are three types of errors analyzed in this research, namely careless errors, concept errors, and test-taking errors. This research is qualitative descriptive research. Subjects’ research included 51 junior high school students, 27 male and 24 female. The research data were obtained from a test instrument of proportion topic consisting of 3 essay questions. The results of the research analysis showed that in problem 1 as many as 3.91% of students made first type error, 11.76% for second type, and 33.33% for third type. In problem 2 as many as 7.84% of students made first type error, 41.18% for second type, and 7.84% for third type. Whereas in problem 3 as many a s 0% of students made first type error, 21.57% for second type, and 62.75% for third type. Teachers need to design effective learning so that students’ errors can be decreased.